Governmentalities of mobility: The role of housing in the governance of Australian rural mobilities. (December 2015) - Dufty-Jones, Rae
Abstract: While mobility has long been recognised to be a core dynamic affecting the consumption of rural housing very little is known about the politics that exist around the connections between mobility and rural housing. To investigate how mobility informs policy approaches to rural housing in Australia this paper brings together the concepts of the politics of mobility and governmentality. Through a case study examining housing policy discourses relating to rural and regional Australia from 1985 to 2000, this paper analyses the way in which various governmentalities of mobility have infused Australian rural housing policy. The paper finds that, during this period, mobility was an important governmental rationality informing Australian regional development and rural housing policies. This study contributes to the critical engagement with the mobility turn in contemporary rural studies by showing that a particular dimension of the mobility turn – the politics of mobility – can be augmented through the application of governmentality theory. Such an analytical approach enables a critical assessment of how such governmentalities of mobility contribute to constructions of the rural as problematic and the implications of such representations for rural regions and communities. Highlights: Explores the governmentalities of mobility in rural housing policy. The politics of mobility can be augmented through governmentality theory. Rural mobility performances are problematised as contributing to regional decline. Housing policies are constructed as contributing to or solving mobility problems. Governmentalities of mobility are used to construct rural communities as deficient.